Removing BOD, COD, and Decolorization of Batik Cual Wastewater using Fenton Mechanism - Gusa, Rika Favoria; Sari, Diana Novita; Afriani, Fitri; Sunanda, Wahri; Tiandho, Yuant (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
During the production of batik cual, thick-colored wastewater is produced. Unfortunately, the wastewater could damage the environment if it is disposed of without specific processing. The Fenton method is an advanced oxidation process (AOPs) that can degrade organic dyes found in liquid waste. In this research, the researchers studied the Fenton mechanism's application to the batik cual wastewater treatment. The Fenton's reagent used was H2O2 with FeSO4.7H2O. Some of the experimental wastewater treatment parameters were the values of biological oxygen demand (BOD), chemical oxygen demand (COD), the degradation efficiency of difficult to decompose organic materials, and the color degradation efficiency in batik cual wastewater. The results show that the Fenton mechanism’s efficiency of removing color from batik cual wastewater is up to 97.8%, COD and BOD removal efficiencies are 76.3% and 75.2%, and the degradation efficiency of difficult to decompose organic matter is 76.8%. Also, the researchers found that the higher amounts of FeSO4.7H2O increase the removal parameters effectiveness. Therefore, the Fenton mechanism can effectively improve the quality of wastewater in batik cual production.